THE ROLE OF THE LINGUOCULTURAL APPROACH IN ENHANCING WRITING COMPETENCE: A SCHOLARLY ANALYSIS ("Conference on Universal Science Research 2023", 2025)
The linguocultural approach has emerged as a vital paradigm in the development of writing competence, especially in the context of second language acquisition and academic discourse. This approach postulates that language is not only a vehicle for communication but a reflection of the underlying cultural constructs that shape societal norms, values, and cognitive processes